Retinal microvascular and neuroretinal structural changes in pulmonary arterial hypertension assessed by OCTA: a comparative study - Erdag, Murat; Caliskan, Tunahan; Yildirim, Hakan; Kivrak, Tarik; Canleblebici, Mehmet; Dal, Ali; Balbaba, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2026)
Background/aim: Pulmonary arterial hypertension (PAH) is a progressive disorder with systemic vasculopathy, and noninvasive assessment remains challenging. The retina, sharing anatomical similarities with the cerebral microcirculation, is an accessible site for visualizing systemic vascular compromise. This study quantitatively evaluated retinal microvascular and neuroretinal structural changes in PAH patients compared to healthy controls using optical coherence tomography angiography (OCTA). Materials and methods: In this single-center, cross-sectional case-control study, 40 patients with group 1 PAH and 38 healthy controls were enrolled. For statistical independence, only the right eye of each participant was analyzed (total: 78 eyes). All participants underwent high-resolution OCTA imaging. Key metrics including vascular density (VD) in the superficial (SCP) and deep capillary plexus (DCP), foveal avascular zone (FAZ) flow density (FD), and neuroretinal thicknesses (ganglion cell complex [GCC] and retinal nerve fiber layer [RNFL]) were quantified and compared using nonparametric tests. Results: Comparison of PAH patients and controls revealed significantly reduced VD in the PAH group. In the SCP, VD was significantly lower in the whole image (p = 0.004) and the ETDRS grid (p = 0.005). Similarly, the DCP showed reduced VD in the whole image (p = 0.006). Quadrant analysis indicated marked reduction in the superior quadrant for both plexuses (p < 0.01). While FAZ area was similar between the groups (p = 0.779), FAZ FD was significantly decreased in PAH patients (p = 0.001). Structurally, mean GCC thickness was significantly reduced (p = 0.006), but RNFL thickness remained preserved (p = 0.267). Conclusion: PAH is associated with significant retinal microvascular density reduction across all plexuses. These findings provide evidence corroborating the systemic nature of PAH vasculopathy. OCTA is a promising noninvasive tool for assessing systemic microvascular involvement in this population. However, further longitudinal studies are needed to validate its utility for disease monitoring.
Keywords: Pulmonary arterial hypertension; optical coherence tomography angiography; retinal microvasculature; vascular density; systemic microvasculopathy